1984
DOI: 10.1159/000194697
|View full text |Cite
|
Sign up to set email alerts
|

Influence du tabagisme chronique sur les leucocytes

Abstract: The authors showed a significant increase in total leukocyte count (2p < 0.001), neutrophil concentration (2p < 0.001) and lymphocyte concentration (2 p < 0.01) in 21 chronic smokers compared to 22 non-smokers. However, only the total leukocyte count and the neutrophil count proved to be correlated to carboxyhemoglobin saturation. Slightly different hypotheses are proposed to explain the increase in leukocyte count: the carbon monoxide and/or the carboxyhemoglobin acts directly on peripheral blood leukocytes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…38 We confirmed the previously reported increase in total leucocyte blood counts and the size of the increase in smokers compared with non-smokers [6][7][8][9][10][11][12][13][14][15] and the negative relation between the total leucocyte blood count and lung function in smokers. [15][16][17][18][19] The total leucocyte blood counts independently accounted for about 3% of the variation of FEV 1 residuals and this eVect of leucocytes on lung function makes this figure unsuitable for predicting accelerated loss of lung function in smokers.…”
Section: Discussionsupporting
confidence: 90%
“…38 We confirmed the previously reported increase in total leucocyte blood counts and the size of the increase in smokers compared with non-smokers [6][7][8][9][10][11][12][13][14][15] and the negative relation between the total leucocyte blood count and lung function in smokers. [15][16][17][18][19] The total leucocyte blood counts independently accounted for about 3% of the variation of FEV 1 residuals and this eVect of leucocytes on lung function makes this figure unsuitable for predicting accelerated loss of lung function in smokers.…”
Section: Discussionsupporting
confidence: 90%
“…The absolute number of T cells and surface IgG-bound B lymphocytes was also increased in smokers in accordance with the literature [21,22], In the present study we have demonstrated a higher number of spleen cells in mice kept in cigarette smoke, an increase which was more definite calculating the cell number per milligram spleen. This alteration in the number of immunocompe tent cells might be connected with the irritat ing effect of tobacco smoke, inducing chronic inflammations and sometimes allergic reac tions; this may contribute to the increase of various immunoglobulin levels, too.…”
Section: Discussionsupporting
confidence: 93%
“…The number of cigarettes consumed on the test day was 7 (0-8), and the time between smoking the last cigarette and providing the breath and blood samples was 1.0 (0. [6][7][8][9][10][11][12][13][14] hours.…”
Section: Resultsmentioning
confidence: 99%